2017
DOI: 10.1186/s12931-017-0514-0
|View full text |Cite|
|
Sign up to set email alerts
|

Imatinib relaxes the pulmonary venous bed of guinea pigs

Abstract: BackgroundRecently, the IMPRES study revealed that systemic imatinib improves exercise capacity in patients with advanced pulmonary arterial hypertension. Imatinib blocks the tyrosine kinase activity of the platelet-derived growth factor (PDGF)-receptor (PDGFR), acts antiproliferative and relaxes pulmonary arteries. However so far, the relaxant effects of imatinib on pulmonary veins (PVs) and on the postcapillary resistance are unknown, although pulmonary hypertension (PH) due to left heart disease (LHD) is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 90 publications
(121 reference statements)
3
37
0
Order By: Relevance
“…imatinib relaxes the pulmonary arterial bed of healthy and pulmonary hypertensive rats [ 5 , 6 ]. Within this context, the relaxant effects of TKIs appear to be not limited to the pulmonary arterial bed, as imatinib, just as the PDGFR-β-inhibitors SU6668 or DMPQ also relax pulmonary veins (PVs) [ 7 ]. With regard to imatinib, it even exerts pulmonary venous relaxation if it is inhaled [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…imatinib relaxes the pulmonary arterial bed of healthy and pulmonary hypertensive rats [ 5 , 6 ]. Within this context, the relaxant effects of TKIs appear to be not limited to the pulmonary arterial bed, as imatinib, just as the PDGFR-β-inhibitors SU6668 or DMPQ also relax pulmonary veins (PVs) [ 7 ]. With regard to imatinib, it even exerts pulmonary venous relaxation if it is inhaled [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, the relaxant effects of TKIs appear to be not limited to the pulmonary arterial bed, as imatinib, just as the PDGFR-β-inhibitors SU6668 or DMPQ also relax pulmonary veins (PVs) [ 7 ]. With regard to imatinib, it even exerts pulmonary venous relaxation if it is inhaled [ 7 ]. The dual action of imatinib on pulmonary vascular remodelling and vessel tone [ 2 , 5 7 ] is still more remarkable, as PDGF-BB also contracts PVs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelet‐derived growth factors (PDGFs) and their receptors (PDGFRs) have served as prototypes for growth factor and receptor tyrosine kinase (Andrae, Gallini, & Betsholtz, ). Thus, treatment with Imatinib, (PDGF receptor antagonist) have considered reducing right ventricular pressure, pulmonary proliferation by suppressing activation of downstream signaling pathways in guinea pigs (Maihöfer et al, ). Furthermore, the clinical investigations reported that treatment with Imatinib has shown significant improvement in 6 min walk test and hemodynamics in pulmonary hypertensive patients through vasodilation potential (Minami et al, ).…”
Section: Pharmacological Interventions and Their Molecular Aspectsmentioning
confidence: 99%